Contemporary rates and outcomes of single- vs. dual-coil implantable cardioverter defibrillator lead implantation: data from the Israeli ICD Registry. Issue 9 (4th October 2016) - Leshem, Eran; Suleiman, Mahmoud; Laish-Farkash, Avishag; Konstantino, Yuval; Glikson, Michael; Barsheshet, Alon; Goldenberg, Ilan; Michowitz, Yoav; ,
Abstract: Aims: Dual-coil leads were traditionally considered standard of care due to lower defibrillation thresholds (DFT). Higher complication rates during extraction with parallel progression in implantable cardioverter defibrillator (ICD) technology raised questions on dual coil necessity. Prior substudies found no significant outcome difference between dual and single coils, although using higher rates of DFT testing then currently practiced. We evaluated the temporal trends in implantation rates of single- vs. dual-coil leads and determined the associated adverse clinical outcomes, using a contemporary nation-wide ICD registry. Methods and results: Between July 2010 and March 2015, 6343 consecutive ICD ( n = 3998) or CRT-D ( n = 2345) implantation patients were prospectively enrolled in the Israeli ICD Registry. A follow-up of at least 1 year of 2285 patients was available for outcome analysis. The primary endpoint was all-cause mortality. Single-coil leads were implanted in 32% of our cohort, 36% among ICD recipients, and 26% among CRT-D recipients. Secondary prevention indication was associated with an increased rate of dual-coil implantation. A significant decline in dual-coil leads with reciprocal incline of single coils was observed, despite low rates of DFT testing (11.6%) during implantation, which also declined from 31 to 2%. In the multivariate Cox model analysis, dual- vs. single-coil lead implantation was not associated with an increased risk of mortality [hazard ratio (HR) = 1.23; P = 0.33], heart failure hospitalization (HR = 1.34; P =0.13), appropriate (HR = 1.25; P = 0.33), or inappropriate ICD therapy (HR = 2.07; P = 0.12). Conclusion: Real-life rates of single-coil lead implantation are rising while adding no additional risk. These results of single-coil safety are reassuring and obtained, despite low and contemporary rates of DFT testing.